In a Real-Life Setting, Direct-Acting Antivirals to People Who Inject Drugs with Chronic Hepatitis C in Turkey - Sarıgül Yıldırım, Figen; Üser, Ülkü; Sarı, Nagehan Didem; Kurtaran, Behice; Önlen, Yusuf; Şenateş, Ebubekir; Gündüz, Alper; Zerdali, Esra; Karsen, Hasan; Batırel, Ayşe; et al. (Turkish Journal of Gastroenterology, 2022)
Background: People who inject drugs (PWID) should be treated in order to eliminate hepatitis C virus in the world. The aim of this study was to compare direct-acting antivirals treatment of hepatitis C virus for PWID and non-PWID in a real-life setting. Methods: We performed a prospective, non-randomized, observational multicenter cohort study in 37 centers. All patients treated with direct-acting antivirals between April 1, 2017, and February 28, 2019, were included. In total, 2713 patients were included in the study among which 250 were PWID and 2463 were non-PWID. Besides patient characteristics, treatment response, follow-up, and side effects of treatment were also analyzed. Results: Genotype 1a and 3 were more prevalent in PWID-infected patients (20.4% vs 9.9% and 46.8% vs 5.3%). The number of naïve patients was higher in PWID (90.7% vs 60.0%), while the number of patients with cirrhosis was higher in non-PWID (14.1% vs 3.7%). The loss of follow-up was higher in PWID (29.6% vs 13.6%). There was no difference in the sustained virologic response at 12 weeks after treatment (98.3% vs 98.4%), but the end of treatment response was lower in PWID (96.2% vs 99.0%). In addition, the rate of treatment completion was lower in PWID (74% vs 94.4%). Conclusion: Direct-acting antivirals were safe and effective in PWID. Primary measures should be taken to prevent the loss of follow-up and poor adherence in PWID patients in order to achieve World Health Organization’s objective of eliminating viral hepatitis Cite this article as: Sarıgül Yıldırım F, Üser Ü, Sarı ND, et al. In a real-life setting, direct-acting antivirals to people who inject drugs with chronic hepatitis C in Turkey. Turk J Gastroenterol. 2022;33(11):971-978